Mutation Breeding for Climate Resilient Vegetable Crops Improvement in Qatar - Aisha Al-Kuwari (17714568) (2025)
Qatar's harsh arid climate presents significant challenges for sustainable vegetable production, necessitating the development of climate-resilient crop varieties. This research employs gamma radiation-induced mutagenesis using ⁶⁰Co as a source to generate genetic variation in three economically important vegetable crops: common bean (Phaseolus vulgaris), tomato (Solanum lycopersicum), and maize (Zea mays). The methodology involves systematic radio-sensitivity testing across a dose of 0, 100, 200, 300, 400, 500, and 600 Gy to determine optimal mutation induction parameters. For each crop, LD50 values are established, with subsequent bulk treatments applied at approximately LD30 levels to maximize mutation frequency while maintaining adequate plant survival. Large seed populations are subdivided into replicates to ensure uniform irradiation exposure and statistical validity. Radio-sensitivity testing revealed differential dose responses across the three target crops. Tomato demonstrated highest tolerance, maintaining 100% germination up to 300 Gy before declining to 70% at 600 Gy. Maize showed consistent performance across all doses, maintaining 95-100% germination throughout the range. Common bean exhibited greatest sensitivity, with germination declining progressively from 100% (control) to 25% at 600 Gy, indicating species-specific radiosensitivity patterns essential for optimizing mutation breeding protocols. The dosewas chosen 350 Gy and does rate of Gamma source 14.5 Gym/min. Building upon previous work under TC initiative QAT5008, this study systematically screens advanced mutant populations: tomato (M1 generation), common bean (M3 generation), and sweet corn (M3 generation). Selection focuses on traits conferring tolerance to salinity, heat stress, and water deficit - key environmental constraints in Qatar's agricultural systems. Promising mutant lines undergo evaluation under both controlled greenhouse conditions and saline field environments. Current progress includes documentation of numerous morphological and physiological mutations in M2 populations across all three crops. Advanced generation materials (M4) for beanand sweet corn are undergoing continued selection and purification. Upon reaching homozygosity(M8 generation), elite mutant lines will undergo multi-location field evaluation leading to potential variety release for Qatar's agricultural sector. This research directly supports Qatar National Vision 2030 objectives for food security enhancement and aligns with UN Sustainable Development Goals 2 (Zero Hunger) and 13(Climate Action). The initiative simultaneously builds local capacity in mutation breeding technologies at the Department of Agricultural Research, contributing to long-term agricultural sustainability and innovation capabilities in Qatar. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx